2002
DOI: 10.1046/j.1460-2695.2002.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐cycle rotating bending fatigue property in very long‐life regime of high‐strength steels

Abstract: In order to investigate the fatigue properties of high‐strength steels in the very long‐life regime up to over 109 cycles, cantilever‐type rotating bending fatigue tests were carried out for two kinds of high‐strength steels, SUJ2 and SNCM439, which were machined by grinding and finished by electropolishing after grinding. And also, the residual stress on the specimen surface of the ground specimen was examined by X‐ray diffractometer in order to investigate effects of the residual stress on the fatigue proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 14 publications
(26 reference statements)
11
74
0
2
Order By: Relevance
“…Meanwhile, S content was high in the outer part along the width direction. It is concluded that the inclusion is being changed from MgO·Al 2 At last, the shape of inclusions evolved from irregular into spherical rare earths inclusions.…”
Section: Evolutions Mechanism Of Mgo·al 2 O 3 Inclusions By Cementioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, S content was high in the outer part along the width direction. It is concluded that the inclusion is being changed from MgO·Al 2 At last, the shape of inclusions evolved from irregular into spherical rare earths inclusions.…”
Section: Evolutions Mechanism Of Mgo·al 2 O 3 Inclusions By Cementioning
confidence: 99%
“…Li Jun WANG, 1,2) * Yan Qiang LIU, 3) Qi WANG 1,2) and Kuo Chih CHOU The effect of rare earth metal addition on the non-metallic inclusions in spring steel used in fastener of high speed railway was investigated by metallographic examination; SEM-EDS and component analysis, aiming at deform those harmful inclusions to improve service life of spring steel. MgO·Al 2 O 3 inclusions were found in present experimental steel, which is also confirmed by the stability diagram of MgO/ MgO·Al 2 O 3 /Al 2 O 3 from thermodynamic consideration.…”
Section: Evolution Mechanisms Of Mgo·al 2 O 3 Inclusions By Cerium Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable area formed around the nonmetallic inclusion inside the fish-eye region on the fracture surface was given various names, such as fine granular area (FGA) (1), (9) - (11) and rough surface area (RSA) (14) . The formation mechanism of the GBF area has yet to be elucidated, because it is difficult to directly observe the behavior of subsurface crack initiation and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Their shapes are long and narrow because of the ultrasonic impacts on the surface. EDX (Energy-Dispersive X-ray spectroscopy) results show that they are not typical inclusions, and these high light white areas are nonexistant in un-UNSMed specimens [31][32][33]. An interior crack core of TC4 without severe surface plastic deformation has a circular or elliptical rough area [20].…”
Section: Fatigue Fracture Characteristicsmentioning
confidence: 99%